A new perfusion mode of culture for WJ‐MSCs expansion in a stirred and online monitored bioreactor. Issue 11 (21st August 2021) - Sion, Caroline; Ghannoum, Dima; Ebel, Bruno; Gallo, Fanny; de Isla, Natalia; Guedon, Emmanuel; Chevalot, Isabelle; Olmos, Eric
Abstract: As a clinical dose requires a minimum of 10 6 cells per kilogram of patients, it is, therefore, crucial to develop a scalable method of production of Wharton Jelly mesenchymal stem cells (WJ‐MSCs) with maintained inner characteristics. Scalable expansion of WJ‐MSCs on microcarriers usually found in cell culture, involves specific cell detachment using trypsin and could have harmful effects on cells. In this study,  the performance of batch, fed‐batch, and perfused‐continuous mode of culture were compared. The batch and fed‐batch modes resulted in expansion factors of 5 and 43, respectively. The perfused‐continuous mode strategy consisted of the implementation of a settling tube inside the bioreactor. The diameter of the tube was calculated to maintain microcarriers colonized by cells in the bioreactor whereas empty microcarriers (responsible for potentially damaging collisions) were removed, using a continuous flow rate based on MSCs physiological requirements. Thanks to this strategy, a maximal number of 800 million cells was obtained in a 1.5 L bioreactor in 10 days. Lastly, online dielectric spectroscopy was implemented in the bioreactor and indicated that cell growth could be monitored during the culture. Abstract : In this work, a new perfused‐continuous mode of culture of WJ‐MSCs consisting in the implementation of a settling tube inside the bioreactor was proposed. The removal of used, non‐colonized microcarriers by this tube allowed to reach a maximal number of 800 million of cells in a 1.5 L bioreactor, in 10 days, with an expansion factor of 60. Lastly, on‐line dielectric spectroscopy was implemented in the bioreactor and indicated that cell growth could be monitored during the culture.